Women Leaving the Playpen: The Emancipating Role of Female Suffrage - Michaela Slotwinski; Alois Stutzer (Center for Economic Studies and ifo Institute (CESifo), 2018)
The role of women in Western societies changed dramatically in the 20th century. We study how political empowerment affected women's emancipation as reflected in their life choices like marital decisions and labor market participation. The staggered introduction of female suffrage in Swiss states allows us to exploit the variation in the age women experienced enfranchisement to estimate the differences in life choices between women who were socialized in a world where women had a formal say in politics and those who were mainly socialized before. Our empirical findings document that political empowerment strongly increased female labor force participation, weakened marital bonds and motivated human capital investment. Moreover, being socialized with female suffrage increased long-term voting participation and perceptions of control. Our evidence suggests that changes in formal political institutions hold the power to change norms.
Keywords: D02; D72; J12; J16; J22; J24; Z13; 330; female suffrage; voting rights; institutions; norms; female labor force participation; marital choices; voting participation; efficacy